2017
DOI: 10.1073/pnas.1700917114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear carbonic anhydrase 6B associates with PRMT5 to epigenetically promote IL-12 expression in innate response

Abstract: Interleukin-12 (IL-12) is critical for induction of protective immunity against intracellular bacterial infection. However, the mechanisms for efficient induction of IL-12 in innate response remain poorly understood. Here we report that the B type of carbonic anhydrase 6 (Car6-b, which encoded CA-VI B) is essential for host defense against Listeria monocytogenes (LM) infection by epigenetically promoting IL-12 expression independent of its carbonic anhydrase activity. Deficiency of Car6-b attenuated IL-12 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…The gene expression level was quantified by the RSEM software package. We detected DEGs with the possion distribution method (61), which has been used in previous studies (62)(63)(64). Briefly, given that every gene's expression occupies only a small part of the library, the number of reads from gene A yields to the Poisson distribution.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The gene expression level was quantified by the RSEM software package. We detected DEGs with the possion distribution method (61), which has been used in previous studies (62)(63)(64). Briefly, given that every gene's expression occupies only a small part of the library, the number of reads from gene A yields to the Poisson distribution.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In another study, we demonstrated that there is a likely role for Car6 in immune stimulated lung tissues ( Patrikainen et al, 2016 ) and murine Car6 is likely involved in mucosa maintenance in both airways and gut ( Leinonen et al, 2004 ; Parkkila et al, 1997 ). We formed a preliminary hypothesis that mouse CA VI is involved in immunological functions, which has been confirmed recently ( Xu et al, 2017 ), by showing that CA VI isoform B promotes interleukin-12 expression. However, a gene regulatory function is unlikely for zebrafish CA VI, with the estimated diameter of 15 nm for the pentamer making it too large to enter the nuclear pores.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, BLT1, IL-12p35, IL-12p40, and IL-2 are regulated either directly or indirectly by epigenetic mechanisms. [49][50][51][52][53][54][55] In a future study, we will focus on the molecular mechanisms underlying the differential regulation of cytokine expression in BLT1 hi and BLT1 lo DCs at the intracellular signaling and/or epigenetic levels.…”
Section: Discussionmentioning
confidence: 99%